Study the Role of Electronic Marketing on Business Performance with Emphasis on the Role of Market Orientation - Shirazi, Melika Sadat (International Review of Management and Marketing, 2017)
This study examined the effect of electronic marketing on business performance through the mediating role of market-orientation in the central branch of Mellat Bank. Statistical society of this study consisted of all managers and employees of Mellat Bank in Tehran. According to Krejcie and Morgan Tables, the sample size was 226 and the sampling was done randomly. This descriptive study was correlational and the data collection was done by questionnaire. Likert scale was used to measure the questionnaires. The validity of research tools was approved using a group of experts and and reliability was confirmed using Cronbach’s alpha as 0.878 for electronic marketing, 0.812 for business performance and 0.833 for market orientation. Data were analyzed using structural equation modeling. The results suggest that the electronic marketing components (responsiveness, security, and technology) has a significant effect on business performance. However, effect of security in electronic marketing on business performance has been more compared to other factors. Results also show that market orientation moderates the effect of electronic marketing on business performance. (Incremental) Keywords: Electronic-Marketing, Business Performance, Responsiveness, Security, Technology JEL Classifications: C32; O13; O47